-(x+11)-6=-5(5x+11)-10

Simple and best practice solution for -(x+11)-6=-5(5x+11)-10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(x+11)-6=-5(5x+11)-10 equation:



-(x+11)-6=-5(5x+11)-10
We move all terms to the left:
-(x+11)-6-(-5(5x+11)-10)=0
We get rid of parentheses
-x-(-5(5x+11)-10)-11-6=0
We calculate terms in parentheses: -(-5(5x+11)-10), so:
-5(5x+11)-10
We multiply parentheses
-25x-55-10
We add all the numbers together, and all the variables
-25x-65
Back to the equation:
-(-25x-65)
We add all the numbers together, and all the variables
-1x-(-25x-65)-17=0
We get rid of parentheses
-1x+25x+65-17=0
We add all the numbers together, and all the variables
24x+48=0
We move all terms containing x to the left, all other terms to the right
24x=-48
x=-48/24
x=-2

See similar equations:

| 118=4(2p+7)+7p | | 4+7x=-20-3x | | 10k-14k-6=-38 | | 2(4x+4)=−2x−32 | | 6a+11=53 | | 4/3=16/m | | 7(w-2)=5w+20 | | 0=2k+2k | | 5^2x-5^x+1+2=0 | | 13x^2+5x-300=0 | | 20/x+3=5/2 | | -18=3b-3b | | c+3.7=5.5 | | 2x(x)=90 | | x/3+4=21 | | 9(a+11)=-11(a-9) | | 4/5+3m/5=41/15 | | 4x-(x+6)+8=2 | | x(x)-3x+0=0 | | -8(7-5n)=264 | | d-(-14)=9 | | 6(f+5)+8=32 | | -9(-4x-4)=-9x-(1-8x) | | x+5+1=-1 | | 3(x-5)=117 | | x2-3x+0=0 | | 3(3+x)=117 | | 11.21+0.1u=-1.6u-9.02 | | h-9=9h+5=4 | | 12(9-4r)=12(4+r) | | 9x-0.75=0.416 | | 7+5x-8x=16 |

Equations solver categories